PAI TEACHERS' STRATEGIES IN INTERNALIZING THE VALUE OF RELIGIOUS MODERATION IN STUDENTS AT SMK-SMTI KOTA BANDA ACEH - Elisa Nur Pratiwi; Marzuki Abu Bakar (SOSIOEDUKASI, 2025)
This research is motivated by the challenges of religious moderation in Indonesia, especially in Aceh, which is known for the application of Islamic Sharia and religious diversity. The purpose of this study is to explore the strategies of Islamic Religious Education (PAI) teachers in internalizing the value of religious moderation in SMK-SMTI Banda Aceh, a vocational school that reflects this diversity. The research method used is a qualitative approach with a case study design, involving observation, in-depth interviews, and documentation to dig into information in depth. The results of the study show that the religious moderation policy in schools has been implemented effectively through equal treatment for students from various religious backgrounds and the internalization of moderation values in PAI learning. PAI teachers play an important role in relating the material to students' daily experiences, so that students can apply the value of moderation in social interactions. The conclusion of this study confirms that the internalization of the value of religious moderation not only strengthens academic understanding, but also forms the positive character of students who are ready to face diversity in society. These findings show the importance of education that prioritizes the values of religious moderation as a foundation for creating a more tolerant and inclusive society in the future.